Estimation of the primary air pollutant emission levels of in-use gasoline vehicles and their influencing factors in Beijing, China - Yangyang Cui; Yan Shen; Lijun Zhu; Huawei Yi; Guanghan Huang; Han Li; Linzhen Qu; Aijun Shi; Yifeng Xue (Atmospheric Environment: X)
Gasoline vehicles (GVs) have become one of the main emission sources of NOx and volatile organic compounds (VOCs) in Beijing, and determining the pollutant emission levels of in-use GVs is crucial. In this study, we assessed the emission levels, exceedance rates, and factors influencing primary air pollutants (NO, CO, and hydrocarbons (HCs) from GVs, including 7.46 million GVs in Beijing from 2019 to 2023. We predicted the variation in the exceedance rate after implementing the standard b-limit and assessed the social stability risk. In general, the emissions of GVs in Beijing were relatively low. According to the simple driving mode conditions, the CO, HC and NO concentrations in the top 50% of the cumulative probability distributions of emissions were 0.04%, 10.3 ppm and 77.0 ppm, respectively, which account for only 1/10∼1/8 of the standard a-limit values. However, we found that the pollutant concentrations corresponding to the top 10% and 90% of the cumulative probability distributions significantly differed. For example, the NO concentrations in the top 10% were 220 times greater than those in the top 90%, namely, approximately 36.5% greater than the standard limit. The greater risk of exceeding the standards was related to the occurrence of carbon deposits on the valves and cylinder heads of engines, of which medium-duty trucks (MDTs) exhibited the highest rate of exceeding the standards (34.5%) due to vehicle deterioration under high-intensity use. GVs exhibited the highest exceedance rate among all the vehicle types, at 38.7%, whereas China VI vehicles exhibited an exceedance rate of only 0.2%. If the more stringent standard b-limit were implemented, the number of vehicles exceeding the standard would increase, and the exceedance rate of GVs under the standard b-limit would be slightly greater than that under the a-limit. Overall, the exceedance rate showed a decreasing trend with increasing emission stage, with the proportion of the exceedance rate at the different emission stages also varying.